80SiO2‐20LaF3 oxyfluoride glass ceramic coatings doped with Nd3+ for optical applications. (29th December 2017) - Gorni, Giulio; Balda, Rolindes; Fernández, Joaquín; Velázquez, Jose J.; Pascual, Laura; Mosa, Jadra; Durán, Alicia; Castro, Yolanda
Abstract: Transparent glass ceramic (GC) films and self‐supported layers of composition 80SiO2 ‐20LaF3 doped with Nd 3+ were prepared by sol‐gel method for the first time. GC films were deposited by dip coating on different substrates and heat‐treated between 350°C and 850°C for 1, 3, and 80 hours. The structural analysis of thin films was performed by GI‐XRD and HR‐TEM to check the LaF3 nanocrystals precipitation in the SiO2 matrix, revealing a crystal size lower than 5 nm. The emission and excitation spectra and lifetimes of the films have been obtained for different thermal treatments and Nd 3+ contents. The luminescence intensity of the 4 F3/2 → 4 I11/2 laser transition increases with the treatment temperature and Nd 3+ content, whereas a reduction for the luminescence lifetime is observed compared to those observed in bulk samples prepared by melting quenching.